2020
DOI: 10.1016/j.gie.2020.03.595
|View full text |Cite
|
Sign up to set email alerts
|

731 Endoscopic Ultrasound-Guided Gallbladder Drainage (Eus-Gb) Compared to Percutaneous Gallbladder Drainage (Pc-Gb) for High-Risk Non-Surgical Patients With Acute Cholecystitis: A Large Academic Tertiary Care Center Experience

Abstract: Background and Aim: Walled off pancreatic necrosis (WON) is an important complication of acute necrotizing pancreatitis (ANP). There are limited data on comparison of nasocystic irrigation versus lumen apposing metal stent (LAMS) in management of WON. We compare the technical and clinical success of both the treatment strategies. Material and Methods: A randomized controlled trial conducted on patients with ANP with symptomatic WON who were randomized to nasocystic irrigation with hydrogen peroxide (group A) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Screening the titles and abstracts yielded 27 studies for detailed review. Ultimately, we found 11 eligible studies based on inclusion and exclusion criteria [5][6][7][12][13][14][15][16][17][18][19]. Figure 1 illustrates the flow chart for the literature search and study selection.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Screening the titles and abstracts yielded 27 studies for detailed review. Ultimately, we found 11 eligible studies based on inclusion and exclusion criteria [5][6][7][12][13][14][15][16][17][18][19]. Figure 1 illustrates the flow chart for the literature search and study selection.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Figure 1 illustrates the flow chart for the literature search and study selection. Among the 11 studies included in the meta-analysis, there were 8 retrospective studies [5,7,[12][13][14][16][17][18], one of them being a propensity-matched cohort study [19] and 3 prospective studies (One prospective cohort study and two randomized controlled trials) [6,15,19]. Seven of the 11 studies were full-length articles [5][6][7]15,16,18,19] and the remaining 4 studies were published as abstracts; however, the data on outcomes were reported [12][13][14]17].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations